PERANCANGAN ROBOT PENGHINDAR HALANGAN MENGGUNAKAN SENSOR ULTRASONIK BERBASIS MIKROKONTROLER AT89S51 - Supardi, I Wayan; Wendri, Nyoman; Sarasmitha, N. L. P. (BULETIN FISIKA, 2013)
It has been   designed   and fabricated   robot   obstacle avoidance   using   ultrasonic   Sensors based microcontroller   AT89S51 . Ultrasonic sensors to function as an input that will beprocessed by the   microcontroller   AT89S51   to   turn on or   turn off the   motor .Obstacleavoidance robot consists  of   three   pairs of   ultrasonic   sensors , where a pair of ultrasonic sensors consist of a series of sensor transmitter   and   receiver   sensor   circuit , a DC motor drive  circuit  and the minimum system using IC AT89S51. Transmitter and receiver sensors ultrasonic sensors placed side by side, at a distance of 10 cm or less than 10 cm where tension is 900 mV or more than 900 mV robot  will  turn.